2023
DOI: 10.1002/adma.202306763
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Clean Hydrogen Gas from Waste Plastic at Zero Net Cost

Kevin M. Wyss,
Karla J. Silva,
Ksenia V. Bets
et al.

Abstract: Hydrogen gas (H2) is the primary storable fuel for pollution‐free energy production, with over 90 million tonnes used globally per year. More than 95% of H2 is synthesized through metal‐catalyzed steam methane reforming that produces 11 tonnes of CO2 per tonne H2. “Green H2” from water electrolysis using renewable energy evolves no CO2, but costs 2–3x more, making it presently economically unviable. Here  we report catalyst‐free conversion of waste plastic into clean H2 along with high purity graphene. The sca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Meanwhile, new technologies may offer a pathway to the creation of products of added value. For instance, Wyss et al (2023) demonstrated how plastic waste can be converted into clean H 2 along with high purity graphene. This idea and technique could be applied to EOL fishing gear, as Eimontas et al (2023) indicated its suitability as a feedstock for additional higher added value energy product generation.…”
Section: Opportunities To Promote a Circular Economymentioning
confidence: 99%
“…Meanwhile, new technologies may offer a pathway to the creation of products of added value. For instance, Wyss et al (2023) demonstrated how plastic waste can be converted into clean H 2 along with high purity graphene. This idea and technique could be applied to EOL fishing gear, as Eimontas et al (2023) indicated its suitability as a feedstock for additional higher added value energy product generation.…”
Section: Opportunities To Promote a Circular Economymentioning
confidence: 99%
“…Furthermore, in the case of gasification and steam reforming, the feedstock can be transformed into a gas with a high hydrogen content. Finally, we can cite the processes intended to produce hydrogen and carbon materials from plastics, as in the case of microwave-assisted catalytic pyrolysis [29] or flash Joule heating [30]. In this section, the main chemical treatment processes will be presented, with a focus on pyrolysis.…”
Section: Alternative Plastic Waste Treatment Processesmentioning
confidence: 99%
“…With this technique, they succeeded in extracting 97% of the hydrogen content of plastics. In another study, Wyss et al [30] applied an FJH process to produce hydrogen and graphene from different types of plastics, with hydrogen extraction efficiencies exceeding 80%.…”
Section: Combined Carbonaceous Materials and Hydrogen-production-orie...mentioning
confidence: 99%
“…However, the resulting pyrolysis oil and gas face several issues, including poor quality and high costs associated with separation and purification. These issues limit the widespread commercial application of these pyrolysis products [ 33 ]. Stable and high-value carbon materials can be produced through the co-pyrolysis of waste plastics and biomass materials, making it a promising strategy.…”
Section: Introductionmentioning
confidence: 99%